power efficiency, power intensity of products, the division of general power, multifood production. - Kuts G.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2010)
The analysis of the use thermal secondary power resources (TSPR) was carried out. The possible thermal circuits for connecting TSPR to the urban heating networks of housing sector were examined. Three variants of scheme - serial, parallel, and parallel-serial — were recommended. Choice of scheme is determined by parameters of heat carrier from TSPR recovery (temperature, pressure, hourly capacity).Detailed circuits for recovering the heat of thermal secondary power resources sources with recommendations for choosing the best version are given. It is examined a question of the creation of industrial centers in cities where the enterprises of iron-and-steel, chemical, and petrochemical industries, oil-refining and by-product coke plants are situated. It is recommended for the enterprises with Cogeneration Heat Plant or large Heat Plant to use blocking- scheme, when within town's closed hot-water supply scheme part of feed-back water from district heat plant returns to the enterprise, where it again heating-up with renewable energy sources and next with steam from the boiler. The scheme allows use low and high potential heat energy from renewable sources.Industrial centers of heat supply are formed on the basis of urban and industrial heat generating sources connecting all types of heat recovery units of high and low potential TSPR. It is possible to cover 50—70 % of heat load for heating in winter and full load for hot water in summer due to connecting TSPR of enterprises to urban heat supply systems.The data of yield and the use of TSPR by enterprises of energy-intensive industries for the near-term are given. Possible traditional fuel substitution may reach in 2010 up to 1845—2060 thousand tce, and in 2015 — 2070—2450.